Person Identification Based On Handwriting - sugandhi, Sushma; Patil, Vinita (International Journal of Computer Sciences and Engineering, 2019)
This design, implementation, and evaluation of a research work for developing an automatic person identification system using hand written biometric. The developed automatic person identification system mainly used toolboxes provided by MATLAB environment. . In order to train and test the developed automatic person identification system, an in-house hand written database is created, which contains hand signatures of different persons . The collected hand data have gone through pre-processing steps such as producing a digitized version of the signatures using a scanner, converting input images type to a standard binary images type, cropping, normalizing images size, and reshaping in order to produce a ready-to-use hand signatures database for training and testing the automatic person identification system. Global features such as signature height, image area, pure width, and pure height are then selected to be used in the system. For features training and classification, the support vector machine(SVM) is used.